Assessment of Ferritin Level In Covid‐19 Patients: Does It Predict Severity? Life Sciences-Medicine for Novel Therapy - Elamin, Mohamed Osman; Elamin. A, Almathani Mubarek.; Kheir, Musa Mohamed; Noor, Sufian Khalid; Osman, Ahmed A.; Natto, Hatim Abdullah; Elshareef, Awadelkareem A.A.; Elamin, Fowzi O.; Alshehri, Ali .M. (International Journal of Life Science and Pharma Research, 2022)
Corona-virus disease‐2019 (COVID‐19) increased burdens on health systems. A hyper inflammatory response including high ferritin has been a hallmark of COVID‐19 infection and is thought to be a key mediator of morbidity and mortality. We aimed to measure ferritin level and investigate its correlation with disease severity and outcome of Sudanese COVID-19 patients. A prospective study enrolled 100 COVID-19 patients in Khartoum state during the period from July to October 2020. We collected participants’ data regarding demographics, clinical presentations, comorbidities, disease severity, and clinical courses during hospitalization, and outcomes. Serum ferritin level was measured for all patients and ferritin level more than 250 μg/L was considered elevated. Among 100 patients, 68(68%) were males, the most common age group was 51-70 years 58(58%). The major comorbidities were Hypertension 48 (48%) and DM 47 (47%). Just under half of the patients presented with mild pneumonia (n=45; 45%) and about one-third (n=37; 37%) received mechanical ventilation. Hyperferritinemia (ferritin>250 μg/L) was observed in 74(74%) patients. Additionally, 40(40%) had ferritin levels above 1000 μg/L. High ferritin levels were significantly common among patients with shortness of breath (P. value= 0.002), hypertension (P. value= 0.01), diabetes (P. value= 0.025), chronic renal diseases (P. value= 0.007), cardiovascular disease (P. value= 0.036), smoking (P. value= 0.03), need for mechanical ventilation (P. value= 0.000), and longer hospital stay duration above 7 days (P. value= 0.000). On the other hand, high ferritin level was correlated with severe pneumonia (P. value= 0.000), ARDS (P. value= 0.000) and sepsis (P. value= 0.009). As well, high ferritin level was associated with high mortality (P. value= 0.000). we concluded that the ferritin level was very high among COVID-19 patients and associated with increased severity of the disease and poor outcome.